2013
DOI: 10.1111/dote.12068
|View full text |Cite
|
Sign up to set email alerts
|

Salvage radiation therapy and chemoradiation therapy for postoperative locoregional recurrence of esophageal cancer

Abstract: The purpose of this retrospective study was to assess the efficacy of salvage radiation therapy (RT) or chemoradiation therapy (CRT) for locoregional recurrence (LR) of esophageal cancer after curative surgery. Forty-two patients who received salvage RT or CRT for LR of esophageal cancer after curative surgery between November 2000 and May 2012 were reviewed. The intended RT regimen was 60 Gy in 30 fractions combined with concurrent platinum-based chemotherapy. Median follow-up periods were 17.9 months for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…There have been a few studies on the efficacy of radiotherapy with or without chemotherapy as salvage treatment for postoperative locoregional recurrence of oesophageal cancer. Studies with more than 20 patients are listed in Table 5 11 12 13 14 15 16 24 26 27 28 29 30 31 . In those studies, the reported response rates were generally high, mostly above 70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few studies on the efficacy of radiotherapy with or without chemotherapy as salvage treatment for postoperative locoregional recurrence of oesophageal cancer. Studies with more than 20 patients are listed in Table 5 11 12 13 14 15 16 24 26 27 28 29 30 31 . In those studies, the reported response rates were generally high, mostly above 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, chemoradiotherapy showed beneficial effects on symptomatic control and might improve long-term survival in selected patients 12 13 . To now, several studies have reported the feasibility and efficacy of concurrent chemoradiotherapy in postoperatively recurrent oesophageal squamous cell carcinoma, mostly with three-weekly or four-weekly schedule of chemotherapy 14 15 16 . However, nearly one quarter of patients required a reduction in or omission of the second cycle of chemotherapy 16 .…”
mentioning
confidence: 99%
“…These advances in therapies directed at EC also improve the prognosis of patients with postoperative recurrence of EC. A previous study reported that salvage radiotherapy or CRT for locoregional recurrence after surgery for EC was safe and effective (17). The effectiveness of multimodal therapies involving chemotherapy, salvage surgery, and salvage CRT against recurrent tumors has already been demonstrated (18,19).…”
Section: Discussionmentioning
confidence: 98%
“…The reason may be that, in addition to intensity-modulated radiotherapy, the innovation of chemotherapy protocols may be another factor. [ 6 , 9 11 ] Furthermore, we analyzed the prognostic factors of SRC in patients with lymph node recurrence after radical surgery of esophageal cancer and found that PRC significantly reduced the efficacy of SRC in patients with lymph node recurrence. Similar results were also found in the reports of Jingu et al [ 12 ] The reason may be that the target of the SRC is more pertinency than the PRC, and patients who do not have PRC have a good tolerance to SRC after the recurrence.…”
Section: Discussionmentioning
confidence: 99%